y=1,5x-5. (3 ;0) (0; -5)
Пошаговое объяснение:
y=kx+b
1 = 4k+b
-2= -2k+b. Вычтем из второго уравнения первое:
1-(-2)= 4k-2k+b-b
3=2k
k=3/2
k=1,5. Подставим это значение в первое уравнение
1=4*1,5+b
1=6+b
b= -5
y=1,5x-5
OX: y=0 0=1.5x-5
1.5x=5
x=5/1.5
x=10/3
x= 3 (3
;0)
OY: x=0 y=1,5*0-5
y= -5 (0; -5)
3(x+4y)-4x=2(2x+y)
3x+12y-4x-2*(2x+y)=0
-x+12y-(4x+2y)=0
-5x+12y-2y=0
-5x+10y=0
y=0.5x
7(x-5у)+6x=3(x+4y)+27
7(x-5*(0.5x))+6x=3(x+4*(0.5x))+27
7*(x-2.5x)+6x-3*(x+4*0.5x)-27=0
7*(-1.5x)+6x-3*(x+4*0.5x)-27=0
-10.5x+6x-3*(x+4*0.5x)-27=0
-4.5x-3*(x+4*0.5x)-27=0
-4.5x-3*3x-27=0
-4.5x-9x-27=0
-13.5x-27=0
x=-27/13.5
x=-2
3(x+4y)-4x=2(2x+y)
3(-2+4y)-4*(-2)=2(2*(-2)+y)
-6+12y-4*(-2)-2*(2*(-2)+y)=0
-6+12y-(-4*2)-2*(2*(-2)+y)=0
-6+12y+8-2*(2*(-2)+y)=0
2+12y-2*(2*(-2)+y)=0
2+12y-2*(-4+y)=0
2+12y-(-8+2y)=0
2+12y+8-2y=0
10+12y-2*y=0
10+10y=0
y=-10/10
y=-1
ответ: x=-2; y=-1.
Пошаговое объяснение: